Odpowiedź:
a)
x+ 2x = x + 9
3x -x = 9
2x = 9
x = 9 : 2
x = 4,5
spr.
x + 2x = x + 9
L = x + 2x = 4,5 + 2 * 4,5 = 4,5 + 9 = 13,5
P = x + 9 = 4,5 + 9 = 13,5
13,5 = 13,5
L + P
b)
y + (2y - 5) = 11 - y
y + 2y - 5 = 11 - y
3y +y = 11 + 5
4y = 16
y= 16 : 4
y= 4
spr.
y + 2y - 5 = 11 - y
L= y + 2y - 5 = 4 + 2*4 - 5= 4 + 8 - 5= 12 - 5= 7
P = 11 - y= 11 - 4= 7
7=7
L=P
c)
3a + 4 = (a -1) + (a + 7)
3a + 4 = a - 1 + a + 7
3a + 4 = 2a + 6
3a - 2a = 6 - 4
a = 2
spr.
3a + 4 = (a -1) + (a + 7)
L= 3a + 4= 3*2 + 4= 6 + 4= 10
P = (a - 1) + (a + 7) = (2 -2) + (2 + 7) = 1 + 9 = 10
10=10
L=P
d)
(10 - 2b) + (6 - b) = (10 - b) + (4 - b)
10 - 2b + 6 - b = 10 - b + 4 - b
- 3b + 16 = - 2b + 14
- 3b + 2b = 14 - 16
- b= - 2 /*(-1)
b= 2
spr.
(10 - 2b) + (6 - b) = (10 - b) + (4 - b)
L= (10 - 2b) + (6 - b) = (10 - 2*2) + (6 - 2) = (10 - 4) + 4= 6 + 6 = 12
P= (10 - b) + (4 - b) = (10 - 2) + (6 -2) = 8 + 4= 12
12 = 12
L=P
Szczegółowe wyjaśnienie: